2017
DOI: 10.20321/nilejbe.v3i7.118
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence in Relation to Women Empowerment and Women Household Headship: A Case in Nigeria

Abstract: Domestic Violence against women is very common in both developing and developed countries and is a complex and multi-dimensional phenomenon. However, global developments have yet to be systematically assimilated into theories around violence against women. This study seeks to examine the associations between domestic violence against women household headship and women empowerment in Nigeria. The study used data from the 2013 Nigeria Demographic and Health Survey (DHS). Ordinary least squares (OLS) regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The chi-square analysis results also indicated that intimate partner violence was more prevalent among women with higher education (52.3%) but different results are found in Southeast Nigeria, South Karnataka, Romania, European Union, Spain, Bangladesh, Pakistan, and Tanzania [4250] where women with primary education were the most abused and women's education exhibit strongest association with IPV in a national survey in India [51]. Women's educational achievement can reduce the risk of intimate partner violence for women [52, 53]. Education of women is also an important factor and this study presents that educational level of women is associated with empowerment status of women; therefore women basic and higher education are more empowered but respondents from higher educational attainment are more likely to take their own decisions [13].…”
Section: Discussionmentioning
confidence: 99%
“…The chi-square analysis results also indicated that intimate partner violence was more prevalent among women with higher education (52.3%) but different results are found in Southeast Nigeria, South Karnataka, Romania, European Union, Spain, Bangladesh, Pakistan, and Tanzania [4250] where women with primary education were the most abused and women's education exhibit strongest association with IPV in a national survey in India [51]. Women's educational achievement can reduce the risk of intimate partner violence for women [52, 53]. Education of women is also an important factor and this study presents that educational level of women is associated with empowerment status of women; therefore women basic and higher education are more empowered but respondents from higher educational attainment are more likely to take their own decisions [13].…”
Section: Discussionmentioning
confidence: 99%
“…Domestic violence has been described by studies as an array of abusive or threatening behavior with the purpose of exerting power and maintaining control over the victim, and occurs commonly within the family setting. DV is sometimes interchanged with family violence (Ahmed, Chowdhury & Laskar, 2017;Bamiwuye & Odemegwu, 2014). It includes any attempts by any person in intimate relationship to manipulate, dominate, or use his or her position to exercise control over a person, using fear, threat, intimidation and other forms of abusive behaviours and actions (Segal, Smith, Robinson,& Segal, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic violence against adolescents can be perpetrated in various forms. According to studies, the forms include physical abuse such as flogging, kicking, beating, pushing, slapping, hair pulling, knocking (Derries, Knight, Petzold, Merrill, Williams, & Abrahams, 2018;UNICEF, 2017), sexual abuse, such as unpermitted touches, teasing, forceful intercourse or rape (WHO, 2016;Sinha, Mallik, Sanyal, Dasgupta, Pal, & Murherjee, 2012), verbal abuse expressed as blaming, name-calling, accusations, ranting, and statements that are capable of causing loss of elf-esteem and self-worth (WHO,2017), emotional or psychological abuse (Essein, 2017;Akmatov, 2011), economic abuse such as exploiting an adolescents through street hawking (Nduka & Duru, 2014), dating violence among adolescents involved in intimate relationship (Onanubi, Olumide,& Owoaje, 2017), female genital mutilation (Ahmed, Chowdhury, & Laskar, 2017), and early marriage (WHO, 2017). According to studies, the effects of DV are overwhelming on the victim's physical, mental, social, emotional and reproductive, including exposure to life-threatening diseases like Hepatitis, HIV/AIDS, and other unwholesome conditions and practices such as unwanted pregnancies, unsafe abortions among others Adolescents constitute an appreciable percentage of the general population, and are by nature seen as "seeds' for future generations.…”
Section: Introductionmentioning
confidence: 99%